The myths of Zionism - Rose, John (Pluto Press, 2004)
Scrutinising the roots of the myths of Zionism and mobilising recent scholarship, John Rose shows how many of these stories, as with other mythologies, have no basis in fact. However, because Zionism is a living political force and these myths have been used to justify very real and political ends - namely, the expulsion and continuing persecution of the Palestinians. John Rose separates fact from fiction presenting a detailed analysis of their origins and development. This includes a challenge to Zionism's biblical claims using very recent and very startling Israeli archaeological conclusions.